2007
DOI: 10.1007/s11099-007-0052-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of irradiance, dissolved oxygen concentration, and temperature on the growth of Chlorella sorokiniana

Abstract: The growth response of Chlorella sorokiniana to certain irradiance, DO, and temperature demonstrated the possible causes of low productivity with this strain in outdoor cultures. The growth (biomass productivity) and chlorophyll fluorescence (F v /F m ) were substantially reduced when the dissolved oxygen (above 200 % of air saturation) and temperature were elevated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(75 citation statements)
references
References 15 publications
3
60
0
7
Order By: Relevance
“…For instance, when DO was elevated to a level higher than 13 mg/L, the final biomass concentration was substantially reduced in culture of Chlorella sorokiniana (Ugwu et al 2007), while cell death occurred only when DO reached 36 mg/L for Spirulina platensis Vonshak et al (1996). It is interesting that Euhalothece sp.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, when DO was elevated to a level higher than 13 mg/L, the final biomass concentration was substantially reduced in culture of Chlorella sorokiniana (Ugwu et al 2007), while cell death occurred only when DO reached 36 mg/L for Spirulina platensis Vonshak et al (1996). It is interesting that Euhalothece sp.…”
Section: Discussionmentioning
confidence: 99%
“…However, the experimental design and cultivation conditions in the current study were quite different from the conditions applied in the studies mentioned above (e.g., continuous light (de Bashan et al 2008;Li et al 2011;Park et al 2011b), higher temperature (de Bashan et al 2008;Li et al 2011;Wang et al 2010), and CO 2 injections (Bjornsson et al 2013;Li et al 2011). Some C. sorokiniana species (e.g., CCAP 211/8K the equivalent of UTEX 1230 strain) demonstrated improved performance at elevated temperatures (max at 35-38°C), high light intensity (max at 8000 μmol photons m −2 s −1 ), and CO 2 content (max at 5 % CO 2 ) (Cuaresma Franco et al 2011;Morita et al 2000;Ugwu et al 2007). In addition, algal growth in the current study may be limited by the availability of certain nutrients or light penetration (coming from the top only) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The compounds that are produced in the light-dependent phase (ATP, NADPH) are used in the dark phase to synthesize metabolic molecules essential for growth. Also, it has been reported that some enzymes of the pentose cycle of photosynthesis and CO 2 fixation are inactive during illumination (Bouterfas et al 2006;Ugwu et al 2007).…”
Section: Discussionmentioning
confidence: 99%